ACTIVITY OF DAILY LIVING PADA LANJUT USIA YANG MENDERITA RHEUMATOID ARTHRITIS - Winesha Meilandari; Gamya Tri Utami; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Activity of Daily Living (ADL) is one that affects independence carried out by elderly rheumatoid arthritis every day to meet the needs and demands of everyday life. The experiences joint pain make patients afraid to move so that it interferes with daily activities and can reduce their productivity. This study aims to describe the Activity of Daily Living (ADL) in the elderly who suffered from rheumatoid arthritis. The design of this study uses simple descriptive. Samples were taken by purposive sampling technique that is as many as 74 respondents. The results of this study showed that respondents who experienced elderly activity of daily living suffered from independent rheumatoid arthritis as many as 26 people (43.3%), very low dependent as many as 14 people (18.9%), low dependent as many as 20 people (20.3%) and moderate dependent as many as 14 people (13.6%). It is expected that the elderly who suffer from rheumatoid arthritis understand the level of independent of rheumatoid arthritis in carrying out daily activities.Keywords: Activity of Daily Living (ADL), Elderly, Rheumatoid Arthritis